Chiral phosphoric acid-catalyzed dual-ring formation for enantioselective construction of N–N axially chiral 3, 3′-bisquinazolinones. Issue 94 (9th November 2022) - Pu, Liang-Yuan; Zhang, Yu-Jiao; Liu, Wei; Teng, Fan
Abstract : An efficient, CPA-catalyzed, dual-ring formation strategy to construct a class of N–N axially chiral 3, 3′-bisquinazolinones is reported for the first time. Notably, metal-free reaction conditions were also involved in this procedure. Abstract : In contrast with the well-developed C–C and C–N axial chirality, research focusing on the catalytically asymmetric synthesis of N–N axially chiral compounds is still limited. As a privileged subunit of many antibiotics, the synthesis of N–N axially chiral 3, 3′-bisquinazolinones has not been updated with atroposelective construction. Herein, we firstly report a chiral phosphoric acid-catalyzed dual-ring formation strategy leading to the aforementioned compounds with good chemical yields and enantioselectivities. Notably, metal-free reaction conditions are another advantage of this procedure.